Penerapan Algoritma “LaGrange Interpolating Polynomial” pada Secret Sharing - Lisa Chandra; Yohana Dewi Lulu W; Memen Akbar (UIN Sultan Syarif Kasim Riau, 2012)
PIN (Personal Identification Number) is one of the data that is secrecy and important. Therefore,it is needed technic for keep the secrecy of the data by convert the data from a readable state to apparentnonsense. This technic is called cryptography. One of the cryptography methods is secret sharing. Thispaper will explain how LaGrange Interpolation Polynomial Scheme works on secret sharing. This methodshare a secret data, become some parts that call share (fraction of the secret data) to be shared to peoplethat call participants which being believed to have a right to keep that part of secret. Shares will beingbundle again to create the secret data by using certain methods. By using this application, PIN can beshare securely by an expeditious system. Besides, PIN also more secure in the distribution processbecause the single shares that made by this application does not contain the PIN information itself. Fromthe research and comparable, the application that made is appropriate with the base concept of secretsharing, which there is a threshold that needed to bundle the PIN and if input shares is less than thedefinite threshold, the PIN can’t be decrypted.Keywords: Secret sharing, Shares, LaGrange Interpolation Polynomial, Cryptography.